2013
DOI: 10.1007/s10903-013-9856-y
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Air Quality Survey of Nail Salons in Boston

Abstract: Employees in nail salons, largely Vietnamese immigrant women in Boston, are exposed to a range of volatile organic chemicals from the products used in salons, including solvents, glues and polishes. Some of these chemicals have the potential to cause short and long-term adverse health effects. Only limited research has been performed on assessing occupational exposures. This project aimed to characterize total volatile organic compound (TVOC) and PM2.5 concentrations in nail salons as a function of ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 15 publications
4
37
0
2
Order By: Relevance
“…Adverse health effects observed among NSTs include asthma, dermatitis, and neurological symptoms (Quach et al 2014; Roelofs et al 2008). In addition, some VOCs can form less volatile carbonyls, acids, and oxygenated products that may condense to form secondary organic aerosols that may affect health (Goldin et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Adverse health effects observed among NSTs include asthma, dermatitis, and neurological symptoms (Quach et al 2014; Roelofs et al 2008). In addition, some VOCs can form less volatile carbonyls, acids, and oxygenated products that may condense to form secondary organic aerosols that may affect health (Goldin et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Exposure assessment of nail technicians has been limited by a number of occupational constraints requiring control and characterization including numerous product formulations, limited accessibility to worker populations, and work environments that are often small, confined, and have client visibility. Most research has involved assessing ventilation and educating nail technicians . These studies have found that nail salons with limited ventilation often have the highest levels of total volatile organic compound (TVOC, the sum of VOCs detected with a real‐time instrument) .…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that nail salons with limited ventilation often have the highest levels of total volatile organic compound (TVOC, the sum of VOCs detected with a real‐time instrument) . Nail salons do not always provide appropriate personal protective equipment (PPE), and management and employees have limited knowledge of appropriate health and safety precautions . Only a few studies have assessed worker exposure to VOCs, most finding strong odors and air levels well below occupational exposure limits (OELs) for individual VOCs or mixture of VOCs .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations